2005
DOI: 10.1088/0029-5515/45/11/018
|View full text |Cite
|
Sign up to set email alerts
|

Active control of MHD instabilities by ECCD in ASDEX Upgrade

Abstract: The modification of the stability and the behaviour of core MHD with local electron cyclotron current drive (ECCD) is presented. Starting from the innermost resonant surface, the q = 1 surface, the stability and hence the sawtooth period and the size of sawteeth is controlled with local on/off-axis co-/counter-ECCD. The sawteeth themselves can serve as a trigger for neoclassical tearing modes (NTMs) and therefore the excitation of NTMs can be influenced. Once these NTMs get excited they can be fully stabilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 24 publications
(30 reference statements)
1
63
0
Order By: Relevance
“…ASDEX Upgrade, a medium size divertor tokamak (R 0 = 1.65 m, a = 0.5 m) with an ITERlike cross-section (single-null divertor, elongation up to 1.8, triangularity up to 0.5) and a versatile heating system, including a 140 GHz ECRH system with at present more than 2 MW of installed power, has a strong programme in this area [2], focussed directly on ITER needs. In this paper, we point out the requirements arising from the present theoretical understanding of the control of sawteeth and NTMs by ECCD and then present recent ASDEX Upgrade results that verify the basic predictions from theory.…”
Section: Introductionmentioning
confidence: 99%
“…ASDEX Upgrade, a medium size divertor tokamak (R 0 = 1.65 m, a = 0.5 m) with an ITERlike cross-section (single-null divertor, elongation up to 1.8, triangularity up to 0.5) and a versatile heating system, including a 140 GHz ECRH system with at present more than 2 MW of installed power, has a strong programme in this area [2], focussed directly on ITER needs. In this paper, we point out the requirements arising from the present theoretical understanding of the control of sawteeth and NTMs by ECCD and then present recent ASDEX Upgrade results that verify the basic predictions from theory.…”
Section: Introductionmentioning
confidence: 99%
“…Since both I ECCD and d usually increase with toroidal launch angle, but not with the same power, an optimum toroidal launch angle can be found that maximizes j ECCD . Experiments in ASDEX Upgrade [28] have, by scanning the toroidal launch angle, convincingly verified this optimization strategy. It was found that the power requirement for complete (3,2) NTM suppression was indeed lowest when the current density was maximized, while at even higher launch angle and therefore higher I ECCD but lower j ECCD , the power requirement was found to increase.…”
Section: Progress In Understanding the Physics Of Ntm Stabilization Bmentioning
confidence: 75%
“…Also, first attempts at feedback control of the deposition had been made. Since then, full suppression of the (2,1) NTM has been demonstrated in several devices [27], [28], [29] and feedback control has been developed further. Based on this success, ECCD suppression of NTMs is now a major goal for the ITER ECCD system and recent experimental work has been geared towards establishing the physics base for the design of the ITER ECCD system with respect to this particular point.…”
Section: Application Of Ecrh and Eccd For Optimization Of Plasma Stabmentioning
confidence: 99%
“…Active control of the resistive wall mode (RWM) [53,54] has been demonstrated using magnetic mode detection and applied 3D fields [55][56][57][58][59][60]. Control of the m/n=2/1 neoclassical tearing mode [61,62] has been demonstrated using gyrotrons to drive currents inside the magnetic island [62][63][64][65][66][67]. Furthermore, even when instabilities grow large and result in significant modifications of the plasma state, active control "recovery techniques" can be envisioned, for instance, using ECCD on locked modes in DIII-D [68], or ECH as demonstrated on AUG [69,70] and FTU [69] to recover from locked mode and density limit disruptions.…”
Section: : Introductionmentioning
confidence: 99%